Unity in spite of diversity: heritage as a nation-building strategy in Indonesia - Dachlan, RA (2023)
This thesis examines the use of heritage as a strategy of the state to unite a diverse population into a nation where no prior sense of national belonging existed. Focusing on Indonesia as a case study, this process is explored within the state’s heritage regulatory framework. The thesis examines the construction of national identity through heritage regulations and identifies the state institutions that mobilise their framework. It deploys document analysis for the exploration into the heritage regulations and semi-structured interviews to draw information from people who were directly involved in the framework for their implementation. This thesis argues that heritage is made to construct this notion of identity by creating an image of a nation comprising different regions that are united in spite of the diversity within them. Heritage reinforces the state’s preconceived constitutional notion of culture as a Provincial characteristic. As a result, it may disrupt notions of identity on the ground, especially when the identity it symbolises does not reflect the cultural makeup of the people. In such a case, heritage may communicate a call for conformity; a demand that the culturally diverse people on the ground admit the official notion of cultural identity and internalise it as their own. When there exists a plurality of these identities on the grassroots, this development is more difficult to trace. As heritage in its regulated form becomes less adaptable, its use by state institutions in this way may lead to tension and even resistance among people who feel disinherited by it. In Provinces where the people had a difficult relationship with the government to begin with, heritage may be taken by them as a further affront to a specifically visceral target: their cultural identity. The institutional setup of heritage as a nation-building strategy has mobilised a process that requires long-term management by the state. On the one hand, it is incumbent on the central government of the state to construct a single narrative of Unity in Diversity to project through heritage. But on the other hand, the process to achieve this single narrative is democratised, inviting previously muted voices on the administrative level and on the grassroots, as seen with the adat communities movement’s ideological challenge to this narrative. Thus, in order to maintain heritage as a nation-building strategy, it is incumbent on the state to navigate these competing interests in the long run.